Electrochemical corrosion influencing the Al beryl alloy system subjected to extrusion process - K.G. Sagar; Bincy Rose Vergis; Bharath K. Devendra; P. SampthKumaran (Results in Surfaces and Interfaces)
Aluminum alloys are widely used in various industries due to their affordable properties such as high strength-weight ratio and corrosion resistance. But they are still susceptible to several forms of corrosion, including pitting corrosion, cervices corrosion, intergranular corrosion, and galvanic corrosion. Preventing corrosion in metals may be achieved through several methods such as the use of protective coatings, anodization, use of inhibitors. and the use of corrosion-resistant materials and alloys. The corrosion is quite common in non-ferrous materials especially in aluminum and its alloys. It is therefore imperative to study the mechanical strength, corrosion behaviour etc of non-metals especially aluminum alloys and its composites. Thus, the present work focus on studying the corrosion behaviour of Aluminum metal matrix composites containing Beryl particles and it is taken up in detail. Aluminum Beryl metal matrix composites typically offer better corrosion resistance compared to other metal matrix composites. Beryl is a mineral that consist of beryllium aluminum cyclosilicate extraordinarily strong, dense and stable barrier and provides protection to the aluminum matrix from corroding agents. In this present work Aluminum Beryl composites were produced using casting route and evaluated for corrosion properties, with varying % of beryl (2, 4 & 6 wt%) levels. These alloys composites are then subjected to extrusion process. The sample so prepared are tested for various properties, including hardness, grain size, density, porosity and corrosion resistance. Microstructural and scanning electron microscopic analysis were conducted to examine the surface and structure of the alloy samples. The aluminum 2024 Beryl composites with beryl at 4 levels (2, 4 & 6 wt%) are evaluated in highly corrosive medium (0.5 ml sulfuric acid) and evaluated its corrosion resistance electrochemically. The addition of a beryl particles was effective in mitigating the corrosion with efficacy of about 84.5%. The results demonstrate that the combination of beryl reinforcement to aluminum matrix and adopting extrusion process significantly improve the mechanical properties making them suitable for various applications in industries such as aerospace, automotive and marine.